Natuna in the Lens of Public Creativity: Integration of User-Generated content in an Integrated Marketing Communication Strategy - Krida, Graha Wira; Ariani, Nafiah (Journal of Finance and Business Digital, 2024)
Natuna faces unilateral claims from foreign countries, limited digital infrastructure, and low public participation in building strategic narratives to strengthen public awareness and support sustainable territorial sovereignty. This study wants to find out how User-Generated Content (UGC) can be integrated into an integrated marketing communication strategy (IMC) to increase public awareness and build a strategic narrative that supports Natuna's sovereignty. The purpose of this study is to analyze the role of UGC in modern integrated marketing communication (IMC) strategies, and identify its success factors, UGC-based IMC models to promote Natuna's sovereignty. This research uses integrated marketing communication theory (IMC) to create consistent messaging across different platforms and UGC concepts to increase engagement and authentic narratives in strategic campaigns.